WCZORAJ I DZIŚ DOSKONALENIA NAUCZYCIELI JĘZYKA NIEMIECKIEGO W POLSCE - Zenderowska-Korpus, Grażyna (Neofilolog, 2019)
The main condition for the successful implementation of educational changes and reforms is professional development of teachers. The idea of lifelong learning has a long tradition. This paper presents the main principles of the professional development of teachers of German in Po-land from the 1990s onwards within the framework of the project Del-fort and Polish Association of German Teachers (PSNJN). The author will specify changes in areas and needs in the professional development of foreign language teachers in recent years.